Critical Path Identification and Time Estimation in Construction: Application of PDM and PERT - Gufran Darma Dirawan; Firnawati Firnawati; Umara Hasmarani Risqiayah; Ulfaizahsyahrir Nurfadhila; Dwi Wahyuni Aprianty; Noor Fadhilla Ramadhani (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
This study discusses the importance of scheduling in construction projects, particularly the application of the Precedence Diagram Method (PDM) and the Program Evaluation and Review Technique (PERT) to enhance time efficiency and identify critical activities. Project scheduling is a key element that ensures the project progresses according to plan and is completed on time. PDM serves to illustrate the sequence and interrelationships between activities through node representation, allowing the identification of the critical path. Meanwhile, PERT uses a probabilistic approach with three time estimates to anticipate variations and uncertainties in activity durations. A case study of a health center construction project in Banteang Regency demonstrates that the application of PDM and PERT, compared to the S-curve method, can optimize resource allocation, minimize the risk of delays, and ensure scheduling efficiency. With the support of software like Microsoft Project, the implementation of these two methods is expected to improve project control and ensure timely completion.